Analisis Semiotika Roland Barthes Dalam Film “Dunia Tanpa Suara” - Niken Pambudiasih (Asosiasi Periset Bahasa Sastra Indonesia, 2023)
Film is an influential visual mass communication medium and has various roles. Films usually contain values that have meaning or messages for the audience. Some signs appear in mass communication as messages that have meaning. These signs can be analyzed using sign science or semiotics. This research focuses on Roland Barthes' semiotics, which analyzes the meaning of signs using denotative, connotative, and meta-language or mythical meaning systems. The type of research used is descriptive qualitative. The data sources presented in this research were obtained directly from the research object, namely the film Dunia Without Suara, and other sources such as books and articles related to the focus of this research. The data collection technique in this research is a documentation study of the film Dunia Without Suara. Based on the analysis that has been carried out using Roland Barthes' semiotic theory, several scenes have meaning from circumstances, events, and shortcomings within a person.